2022
DOI: 10.47405/mjssh.v7i6.1533
|View full text |Cite
|
Sign up to set email alerts
|

The Classroom Climate, Students’ Mathematics Achievement, Students’ Knowledge of Cognition and Regulation Cognition: A Mediation Analysis

Abstract: The role of mathematics in development of the branches of science and technology is enormous. The literature reviews revealed among the factors that affect the achievement of students in mathematics subject are classroom climate, students’ knowledge of cognition and regulation cognition. Therefore, this study aims to determine the mediation effect of knowledge of cognition and regulation of cognition on relationship between classroom climate (student cohesiveness, teacher support, involvement, investigation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This is consistent with what MacKewn et al ( 2022) indicated that students with high mathematical abilities excel in fulfilling all activities of cognitive regulation during problem-solving tasks. Contrarily, a study focused on the mediation effect of cognition knowledge and regulation on students' mathematics achievement found that knowledge of cognition mediated the relationship between certain aspects of classroom climate and mathematics achievement, highlighting a stronger influence of cognitive knowledge over regulation in academic performance (Dolinting & Pang, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what MacKewn et al ( 2022) indicated that students with high mathematical abilities excel in fulfilling all activities of cognitive regulation during problem-solving tasks. Contrarily, a study focused on the mediation effect of cognition knowledge and regulation on students' mathematics achievement found that knowledge of cognition mediated the relationship between certain aspects of classroom climate and mathematics achievement, highlighting a stronger influence of cognitive knowledge over regulation in academic performance (Dolinting & Pang, 2022).…”
Section: Discussionmentioning
confidence: 99%